Recent advances in primary cilia in bone metabolism - Lian, Fenfen; Li, Hui; Ma, Yuwei; Zhou, Rui; Wu, Wei (Frontiers in Endocrinology, 2023)
Primary cilia are microtubule-based organelles that are widespread on the cell surface and play a key role in tissue development and homeostasis by sensing and transducing various signalling pathways.The process of intraflagellar transport (IFT), which is propelled by kinesin and dynein motors, plays a crucial role in the formation and functionality of cilia. Abnormalities in the cilia or ciliary transport system often cause a range of clinical conditions collectively known as ciliopathies, which include polydactyly, short ribs, scoliosis, thoracic stenosis and many abnormalities in the bones and cartilage.In this review, we summarise recent findings on the role of primary cilia and ciliary transport systems in bone development, we describe the role of cilia in bone formation, cartilage development and bone resorption, and we summarise advances in the study of primary cilia in fracture healing. In addition, the recent discovery of crosstalk between integrins and primary cilia provides new insights into how primary cilia affect bone.